What do children’s global ratings of oral health and well-being measure? - Jokovic A, Locker D, Guyatt G. (Blackwell Synergy, 2005)
To explore the constructs children incorporate in the responses to global ratings of their oral health (OH) and OH-related overall well-being (OWB)